Treatment effect of idebenone on inspiratory function in patients with Duchenne muscular dystrophy. Issue 4 (29th August 2016) - Buyse, Gunnar M.; Voit, Thomas; Schara, Ulrike; Straathof, Chiara S.M.; D'Angelo, Maria Grazia; Bernert, Günther; Cuisset, Jean‐Marie; Finkel, Richard S.; Goemans, Nathalie; Rummey, Christian; Leinonen, Mika; Mayer, Oscar H.; et al.
Summary: Assessment of dynamic inspiratory function may provide valuable information about the degree and progression of pulmonary involvement in patients with Duchenne muscular dystrophy (DMD). The aims of this study were to characterize inspiratory function and to assess the efficacy of idebenone on this pulmonary function outcome in a large and well‐characterized cohort of 10–18 year‐old DMD patients not taking glucocorticoid steroids (GCs) enrolled in the phase 3 randomized controlled DELOS trial. We evaluated the effect of idebenone on the highest flow generated during an inspiratory FVC maneuver (maximum inspiratory flow; V'I, max(FVC)) and the ratio between the largest inspiratory flow during tidal breathing (tidal inspiratory flow; V'I, max(t)) and the V'I, max(FVC). The fraction of the maximum flow that is not used during tidal breathing has been termed inspiratory flow reserve (IFR). DMD patients in both treatment groups of DELOS (idebenone, n = 31; placebo: n = 33) had comparable and abnormally low V'I, max(FVC) at baseline. During the study period, V'I, max(FVC) further declined by −0.29 L/sec in patients on placebo (95%CI: −0.51, −0.08; P = 0.008 at week 52), whereas it remained stable in patients on idebenone (change from baseline to week 52: 0.01 L/sec; 95%CI: −0.22, 0.24; P = 0.950). The between‐group difference favoring idebenone was 0.27 L/sec ( P = 0.043) at week 26 and 0.30 L/sec ( P = 0.061) at week 52. In addition, during the study period, IFR improved by 2.8% in patients receiving idebenone and worsened by −3.0% among patients on placebo (between‐group difference 5.8% at week 52; P = 0.040). Although the clinical interpretation of these data is currently limited due to the scarcity of routine clinical practice experience with dynamic inspiratory function outcomes in DMD, these findings from a randomized controlled study nevertheless suggest that idebenone preserved inspiratory muscle function as assessed by V'I, max(FVC) and IFR in patients with DMD. Pediatr Pulmonol. 2017;52:508–515. © 2016 The Authors. Pediatric Pulmonology Published by Wiley Periodicals, Inc.